Modern Orthodox Judaism : a documentary history - Eleff, Zev (Lincoln : University of Nebraska Press, 2016)
Modern Orthodox Judaism offers an extensive selection of primary texts documenting the Orthodox encounter with American Judaism that led to the emergence of the Modern Orthodox movement. Many texts in this volume are drawn from episodes of conflict that helped form Modern Orthodox Judaism. These include the traditionalists$1 (Bresponse to the early expressions of Reform Judaism, as well as incidents that helped define the widening differences between Orthodox and Conservative Judaism in the early twentieth century. Other texts explore the internal struggles to maintain order and balance once Orthodox Judaism had separated itself from other religious movements. Zev Eleff combines published documents with seldom-seen archival sources in tracing Modern Orthodoxy as it developed into a structured movement, established its own institutions, and encountered critical events and issues$1 (Bsome that helped shape the movement and others that caused tension within it. A general introduction explains the rise of the movement and puts the texts in historical context. Brief introductions to each section guide readers through the documents of this new, dynamic Jewish expression.s
Orthodox Judaism and the Modern American Experience: Engaging Reform. Charleston Clamorings and Other "Heresies". Living Orthodox Judaism. The Traditional Talmud and Response to Reform Prayer Books. Talking Talmud. The Modified Mahzor. Orthodox Ministry. The Impaired and Itinerant "Rabbi". Defenders of Tradition. An Orthodox Seminary? -- The contest for Modern Orthodox Judaism. The Arrival of Eastern European Immigrants. Resisting a Treifene Medine. Accommodating to a Goldene Medine. Trailblazers. The Revel Revolution. Solomon Schechter and the Orthodox.The Parting of the Ways: Orthodox and Conservative Judaism. Mixed Seating and "Modern Orthodox". Heresy Hunting -- A Modern Orthodox Movement: Becoming Modern Orthodox Jews. A Modern Orthodox Movement. Orthodox, Inc. The Day School. Beyond the School. Yeshiva University. Industrializing Kashrut. Interfaith Dialogue. The Orthodox Synagogue and Rabbinate. Rites of Passage. A More Orthodox Sanctuary? The "New" Orthodox Rabbi. The State of Orthodox Belief. What Does Orthodoxy Relieve? Halakhah, the Modern Orthodox Way? Responding to Tragedies and Triumphs. The Holocaust. Zionism and the State of Israel. Communism, Vietnam, and Soviet Jewry. The Orthodox Family. Ritual Purity and Birth Control. Tay-Sachs: An Ashkenazic "Disease". The Prenuptial Agreement. From Rebbetzin to Rabbah. The Rabbi's Wife. A Female Synagogue Leader. Sliding to the Right and to the Left. The Center under Siege. Sliding to the Right. Sliding to the Left. Reconsidering Modern Orthodox Judaism in a New Century. Loosening Grip. Modern Orthodoxy Reclaimed?
Includes bibliographical references and index.
Master record variable field(s) change: 072
Keywords: Orthodox Judaism -- History; Orthodox Judaism; RELIGION / Judaism / General; RELIGION / Judaism / Orthodox; History; Electronic books